Remote Ischemic Postconditioning in Case of Traumatic Brain Injury: a Review of Experimental and Clinical Studies - N. S. Shcherbak; I. A. Voznyuk (Неотложная медицинская помощь)
Relevance Traumatic brain injury (TBI) remains one of the leading causes of morbidity and mortality worldwide. Despite advances in treatment based on understanding of the mechanisms of brain injury after TBI, there is a clear need for new therapeutic strategies. Remote ischemic postconditioning (RIPostC) can be considered as a non-pharmacological technique to reduce secondary brain damage and improve clinical outcomes in patients with TBI.Aim of study Raising awareness of emergency physicians, neurosurgeons, neurologists, neurophysiologists about the possible use of the concept of RIPostC in patients with TBI.Material and methods To achieve this goal, the Results of clinical and experimental studies of the use of RIPostC after TBI were analyzed. Literature search was carried out in electronic search systems PubMed (https://pubmed.ncbi.nlm.nih.gov), eLibrary (https://elibrary.ru) using the keywords: “traumatic brain injury”, “remote ischemic conditioning”. A systematic search and selection of publications was performed in January–February 2023. The results of the review included patients with an established diagnosis of traumatic brain injury, followed by the use of RIPostC and animals with experimental modeling of TBI in various ways, followed by RIPostC.Conclusion The totality of data suggests that the use of the concept of RIPostC as a non-invasive protective technique in the provision of emergency care for patients with TBI may contribute to limiting secondary brain damage. However, the underlying neuroprotective processes are quite complex and need further study. Establishing the relationship of humoral, neurogenic and inflammatory reactions in response to the use of RIPostC in TBI will contribute to understanding the mechanisms of emerging neuroprotection, help ease the course of the disease and improve the clinical outcome.